Cerebellar Control of Eye Movements. Issue 1 (March 2017) - Beh, Shin C.; Frohman, Teresa C.; Frohman, Elliot M.
Abstract : Background: The cerebellum plays a central role in the online, real-time control, and long-term modulation of eye movements. Evidence acquisition: We reviewed the latest (fifth) edition of Leigh and Zee's textbook, The Neurology of Eye Movements, and literature in PUBMED using the following terms: cerebellum, flocculus, paraflocculus, vermis, oculomotor vermis, dorsal vermis, caudal fastigial nucleus, fastigial oculomotor region, uvula, nodulus, ansiform lobule, eye movements, saccades, ipsipulsion, contrapulsion, smooth pursuit, vergence, convergence, divergence, gaze-holding, down beat nystagmus, vestibulo-ocular reflex (VOR), angular VOR, translational VOR, skew deviation, velocity storage. Results: The cerebellum is vital in optimizing the performance of all classes of gaze-shifting and gaze-stabilizing reflexes. The flocculus-paraflocculus are crucial to VOR gain and direction, pulse-step matching for saccades, pursuit gain, and gaze-holding. The ocular motor vermis and caudal fastigial nuclei are essential in saccadic adaptation and accuracy, and pursuit gain. The nodulus and ventral uvula are involved in processing otolothic signals and VOR responses, including velocity storage. Conclusions: The cerebellum guarantees the precision of ocular movements to optimize visual performance and occupies a central role in all classes of eye movements both in real-time control and in long-term calibration and learning (i.e., adaptation).